Critical behavior and magnetic refrigeration performance of GdGa1−xAlx (0 ≤ x ≤ 0.3) alloys: Simulation and analysis - Amnah M. Alofi (AIP Advances, 2025)
In this paper, we investigate the magnetic and magnetocaloric properties of GdGa1−xAlx (0 ≤ x ≤ 0.3) alloys, focusing on the influence of aluminum (Al) substitution on critical phase transitions and magnetocaloric efficiency. Using the Arrott–Noakes equation and Kouvel–Fisher method, we precisely determined the critical exponents (γ;β for these alloys. These exponents (γ;β are optimized to be (1.00; 0.41), (0.95; 0.41), (1.00; 0.34), and (0.90; 0.40) for the GdGa1−xAlx samples (with x = 0, 0.1, 0.2, and 0.3), respectively. Following the resolution of the Arrott–Noakes equation, the isotherms M(H, T) were simulated. The magnetocaloric effect of the GdGa1−xAlx (0 ≤ x ≤ 0.3) was evaluated, and the temperature-averaged entropy change (TEC) was calculated under various magnetic fields. The results showed that Al doping enhances the initial magnetic entropy change but leads to a faster decline in TEC with increasing temperature. Notably, the GdGa1−xAlx alloys exhibited stable TEC performance, making them promising candidates for magnetic refrigeration applications, where consistent thermal behavior is critical for optimizing energy efficiency. This study highlights the potential of these alloys for practical applications in thermal management and energy conversion technologies.